2000
DOI: 10.1002/1526-4998(200009)56:9<784::aid-ps208>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal effects of imidacloprid on bumblebees,Bombus terrestris (Hymenoptera: Apidae), during a laboratory feeding test

Abstract: A laboratory feeding test was conducted on queenless micro-colonies of three bumblebee workers (Bombus terrestris L) to study the effects of low doses of imidacloprid on pollen and syrup consumption, worker survival, brood size and larval development. Two doses were used: D1 = 10 mg AI kg À1 in syrup and 6 mg AI kg À1 in pollen; D2 was 2.5 times higher in syrup and 2.7 higher in pollen. During 85 days 27, 30 and 29 micro-colonies were reared for control, D1 and D2 treatments respectively.Food consumption was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 10 publications
8
81
1
Order By: Relevance
“…We have found that split colonies tend to be more successful than worker-founded microcolonies not provided with brood (e.g. as used by Tasei et al (2000)) and produce new brood more quickly. Each microcolony was randomly allocated to one of the four D-lupanine concentration treatments.…”
Section: Methods and Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We have found that split colonies tend to be more successful than worker-founded microcolonies not provided with brood (e.g. as used by Tasei et al (2000)) and produce new brood more quickly. Each microcolony was randomly allocated to one of the four D-lupanine concentration treatments.…”
Section: Methods and Resultsmentioning
confidence: 79%
“…However, one must consider that pollinators are also herbivores, and exposure to some secondary compounds in nectar affects adult pollinators (Wright et al 2013), sometimes in similar ways to the effects of insecticide exposure via pollen or nectar (Bryden et al 2013;Tasei et al 2000). Few studies have examined the effect of naturally-occurring plant compounds in the larval food of pollinators, or determined how larval feeding may impact on offspring production or fitness, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Residue intake has been estimated to range from 4.27 to 13.65 ng per bee day −1 (Authority, 2013). Similar doses during chronic exposure to a different neonicotinoid (imidacloprid) were used by Tasei et al (2000), who found in bumblebees reduced survival of workers and less brood production. Rundlöf et al (2015) found 6.7-16 ng ml −1 clothianidin in the nectar store of honeybees foraging in oil rape fields that grow from seeds coated with clothianidin.…”
Section: Resultsmentioning
confidence: 81%
“…Moreover, the risks as scored in the behavior test agree with experiments by other investigators in bumblebees and also in honeybees. Tasei et al (2000) reported in B. terrestris colonies a loss of 10% in worker survival and a significant decline of about 40% in the numbers of adults produced upon exposure to imidacloprid at 6-10 ppb in the syrup and pollen. Similar sublethal effects were also seen in other bumblebee species like Bombus occidentalis and Bombus impatiens: exposure to 30 ppb imidacloprid had a significant negative effect on the foraging rates (Morandin and Winston 2003).…”
Section: Discussionmentioning
confidence: 99%